Designing a dynamic dissolution method: a review of instrumental options and corresponding physiology of stomach and small intestine - Culen, Martin; Rezacova, Anna; Jampilek, Josef; Dohnal, Jiri (Journal of pharmaceutical sciences, 2013)
Development of new pharmaceutical compounds and dosage forms often requires in vitro dissolution testing with the closest similarity to the human gastrointestinal (GI) tract. To create such conditions, one needs a suitable dissolution apparatus and the appropriate data on the human GI physiology. This review discusses technological approaches applicable in biorelevant dissolutions as well as the physiology of stomach and small intestine in both fasted and fed state, that is, volumes of contents, transit times for water/food and various solid oral dosage forms, pH, osmolality, surface tension, buffer capacity, and concentrations of bile salts, phospholipids, enzymes, and Ca(2+) ions. The information is aimed to provide clear suggestions on how these conditions should be set in a dynamic biorelevant dissolution test.
Keywords: farmaceutická chemie; bioequivalence; Pharmaceutical Preparations; in vitro models; žaludek; Intestine, Small; Stomach; Gastrointestinal Tract; bioavailability; Pharmacokinetics; Chemistry, Pharmaceutical; rozpustnost; dynamic dissolution; léčivé přípravky; Animals; lidé; gastrointestinal physiology; dissolution; Humans; zvířata; biorelevant dissolution; gastrointestinální trakt; tenké střevo; gastrointestinal transit; farmakokinetika; Solubility